THE EFFECT OF PERCEIVED SERVICE QUALITY, WORD OF MOUTH AND PRICE QUALITY ON REPURCHASE INTENTION AND CUSTOMER SATISFACTION ON INSTAGRAMABLE RESTAURANT IN JAKARTA UTARA - Tania Tjhin; Fathur Rayhaan; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2021)
The purpose of this study is to analyze whether there is an effect of Perceived Service Quality, Word of Mouth and Price Quality on Repurchase Intention and Customer Satisfaction at Instagramable Restaurants in North Jakarta. The method used for this research is to use a survey method to obtain data through the distribution of questionnaires to people who live in Jakarta. Then, the data that has been collected is analyzed using PLS-SEM assisted by the SmartPls 3.0 program. The number of samples in this study were 100 respondents. The sampling technique of this research is by using convenience sampling. The results showed that Price Quality had a positive effect on Repurchase Intention and Customer Satisfaction. However, from the results of this study, it was found that Perceived Service Quality did not have a positive effect on Repurchase Intention and Customer Satisfaction. The results of this study also show that Word of Mouth has a positive effect on Repurchase Intention, but does not have a positive effect on Customer Satisfaction.